Business and society : stakeholders, ethics, public policy - Lawrence, Anne T.; Hill, Vanessa D.; Weber, James; Wasieleski, David M. (New York, NY : McGraw Hill Education, 2023)
'In a world economy that is becoming increasingly integrated and interdependent, the relationship between business and society is becoming ever more complex. The globalization of business, the emergence of civil society organizations in many nations, and rapidly changing government regulations and international agreements have significantly altered the job of managers and the nature of strategic decision making within the firm. At no time has business faced greater public scrutiny or more urgent demands to act in an ethical and socially responsible manner than at the present'--
Includes bibliographical references and index.
Buku bacaan asas prasiswazah 2023/2024 Fakulti Ekonomi Pengurusan.
Keywords: Social responsibility of business